Vertical Maxillary Growth after Two Different Surgical Protocols in Unilateral Cleft Lip and Palate Patients. (November 2014) - Bakri, Sherif; Rizell, Sara; Lilja, Jan; Mark, Hans
Objective: The aim of the present study was to compare vertical maxillofacial growth in patients born with unilateral cleft lip and palate (UCLP) who were treated using two different surgical protocols. Design: A retrospective cohort study. Subjects: We studied 92 patients with complete UCLP (61 male and 31 female) treated at Sahlgrenska University Hospital in Gothenburg, Sweden: 46 consecutive patients born between 1965 and 1974 who underwent surgical treatment according to the Wardill-Kilner (W-K) protocol and 46 consecutive patients born between 1982 and 1989 who underwent surgical treatment according to the Gothenburg delayed hard palate closure (DHPC) protocol. Methods: We analyzed lateral cephalograms obtained at 10 years of age. Results: Patients treated according to the Gothenburg DHPC protocol had significantly greater anterior upper facial height, anterior maxillary height, overbite, and inclination of the maxilla than those treated with the W-K protocol. Both techniques led to similar posterior upper facial height. Conclusion: The Gothenburg DHPC protocol in patients with complete UCLP results in more normal anterior maxillary vertical growth and overbite and therefore increased maxillary inclination at 10 years of age.